Cucumber mosaic virus-induced gene and microRNA silencing in water dropwort (Oenanthe javanica (Blume) DC) - Zhen He; Shuangyu Sheng; Lingqi Wang; Tingting Dong; Kun Zhang; Liangjun Li (Plant Methods, 2024)
Abstract Water dropwort (Oenanthe javanica (Blume) DC), an aquatic perennial plant from the Apiaceae family, rich in dietary fibert, vitamins, and minerals. It usually grows in wet soils and water. Despite accumulating the transcriptomic data, gene function research on water dropwort is still far behind than that of the other crops. The cucumber mosaic virus (CMV) induced gene silencing was established to study the functions of gene and microRNA (miRNA) in the water dropwort. CMV Fast New York strain (CMV-Fny) genomic RNAs 1, 2, and 3 were individually cloned into pCB301 vectors. We deleted part of the ORF 2b region and introduced recognition sites. A CMV-induced gene silencing vector was employed to suppress the expression of endogenous genes, including phytoene desaturase (PDS). In order to assess the efficacy of gene silencing, we also cloned conserved sequence of gibberellin insensitive dwarf (GID1) cDNA sequences into the vector and inoculated the water dropwort. The height of CMV-GID1-infected plants was marginally reduced as a result of GID1 gene silencing, and their leaves were noticeably longer and thinner. Additionally, we also used a CMV-induced silencing vector to analyze the roles of endogenous miRNAs. We used a short tandem target mimic approach to clone miR319 and miR396 from water dropwort into the CMV vector. Plants with CMV-miRNA infection were driven to exhibit the distinctive phenotypes. We anticipate that functional genomic research on water dropwort will be facilitated by the CMV-induced gene silencing technique.